(Non-)quoting and subjectivity in online discourse - Lieven VANDELANOTTE (E-REA)
This paper investigates a broad range of quotation practices in social media discourse. Many of these involve so-called non-quotative uses, in which the frame of a conversation or interaction is used fictively to portray and respond to existing attitudes and patterns of behaviour, rather than to actually quote any one specific utterance. Cases considered include Internet memes and tweets incorporating recognizably ‘quotative’ markers such as said no one ever, be like, quotation marks or other known quotation-marking devices, such as source indications preceded by a dash, as well as exchange patterns in which alternating speakers are introduced by means of (pro)nouns followed by colons. The analysis also extends to the many and varied uses of quote tweeting, in which a Twitter user retweets another user’s tweet while simultaneously adding a comment to it. This comment can take many different forms, including further (non-)quotation and more recently also visuals. Collectively the examples surveyed and analysed suggest online discourse reuses and innovates forms of quotation to express subjective responses in both humorous and more politically engaged contexts.